Analysis of Work-Life Balance of Millennial Generation in The Digital Era at PT PNM Mekaar Regional Kediri - Yoyok Erwan Setiono; M. S. Sadana, Stefanus (Management Research Studies Journal, 2025)
This study aims to analyze the work-life balance of the millennial generation in the digital era at PT PNM Mekaar Regional Kediri in order to capture the conditions and implementation of WLB by AO employees that lead to the use of flexibility in terms of time in utilizing technology when working. A qualitative approach with a design thinking model was chosen as the approach and model in this study. The unit of analysis was employees of PT PNM Mekaar Regional Kediri who were included in the millennial generation group with a sample of five employees using purposive sampling. Data collection was carried out by observation, interviews, and think-aloud. The research procedure was carried out by applying a design thinking model consisting of stages in the form of empathize, define, ideate, and prototype. The data analysis technique used NVivo 15. The results of the study describe the results of the interview in the form of a word cloud and the work-life balance of millennial generation employees using the design thinking model. First, empathize, the results obtained that employees need adequate applications, work flexitime, and provide rewards for customers. Second, define, the results obtained that employees are able to distinguish the concept of work and personal life so that the two are not mixed up, but have positions and priorities according to their use. Third, ideate, the results obtained are in the form of four elements of employee needs, including application systems, application features, flexitime, and customer rewards. Fourth, prototype, the results obtained are a description of the application features along with their respective descriptions.